Influence of periodontal treatment on plasma levels of triglycerides, total cholesterol and its components - Parichehr Behfarnia; Ali Reza Tavakoli (Isfahan University of Medical Sciences, 2012)
Abstract Introduction: Periodontitis, a prevalent oral disease, has been associated with several systemic conditions, including lipid metabolism disturbances. The aim of this study was to evaluate the effect of periodontal treatment on decreasing plasma lipids levels. Materials and Methods: In this case/control study sera were collected from 25 adult periodontitis patients and 25 healthy control subjects referring to the Faculty of Dentistry in Isfahan. Plaque indexes, pocket depths, bleeding on probing (BOP), attachment loss (AL) and serum lipid levels (cholesterol, triglyceride, HDL, LDL) were recorded in both groups. Periodontal treatment was carried out only for the test group patients. Six weeks after periodontal treatment, serum lipid levels were measured again in both groups and the results were compared with the initial values (α=0.05). Results: The serum levels of triglyceride, cholesterol, HDL, LDL in the test group before treatment were 156/96,184/64, 49/20, 116/68 mg/dL, respectively, with 121/36, 157/56, 47/85, 114/36, respectively, after treatment. The decreases in triglyceride and cholesterol serum levels were significant but decreases in HDL and LDL levels were not significant. Conclusion: The results of this study indicate that there is a significant relationship between periodontal treatment and a decrease in serum lipid levels. The possible mechanism is the relationship between bacterial endotoxins and induction of proinflammatory cytokines, resulting in changes in the metabolism of lipids, which gives rise to hyperlipidemia. Key words: Cholesterol, Chronic periodontitis, Triglyceride.